Basing Airtankers for Forest Fire Control in Ontario - MacLellan, James I.; Martell, David L. (Operations Research, 1996)
The Ontario Ministry of Natural Resources (OMNR) operates a fleet of nine CL-215 airtankers for forest fire control. The aircraft are based at a small number of airports that serve as home bases, from which they are deployed to a larger set of airports that serve as initial attack bases for fire fighting operations each day. We helped regional fire managers derive subjective airtanker deployment rules that specified how many airtankers were to be deployed at each initial attack base each day. We then developed a mathematical programming model that was used to help identify a home-basing strategy that would minimize the average annual cost of satisfying daily airtanker deployment demands. Our analysis provided OMNR decision makers with valuable insight into airtanker management and was used to help decide where to base the OMNR airtankers for the 1993 and subsequent fire seasons.